The Effect of Screen Time on Delays in Language and Speech Developmental Children: Meta-Analysis - Abida, Liza Laela (jitek, 2024)
Language is a communication tool that humans often use. In the current globalisation era, finding and exchanging information takes effort. This is of course because of progress in the era of globalization, everything has become more accessible and easier because of gadgets Excessive and uncontrolled use of gadgets can have a negative impact on children's psychology and development, especially on their social and communication skills. This research aims to determine the average effect of screen time on language and speech disorders in children. This research is a systematic study and meta-analysis. The articles used in this research were obtained from several databases, including PubMed, Science Direct, and Google Scholar. Based on the results of the case-control study design show that screen time increases language and speech delays in children by 2.67 times compared to no screen time and has statistical significance (p < 0.00001). The cross-sectional subgroup results show that screen time increases language and speech delays in children by 2.64 times compared to no screen time and has statistical significance (p < 0.00001).